Psychological Condition in Facing Existential Crisis Reflected in Gulch’s Song Lyrics - Nofan Ahmad Kholikin; Ana Widiyanti (Metaphor, 2026)
Understanding how music conveys complex psychological experiences requires both literary and semiotic interpretation. This thesis analyzes the existential crisis reflected in the lyrics of the band Gulch, particularly from their albums Burning Desire to Draw Last Breath and Impenetrable Cerebral Fortress. The analysis applies Roland Barthes’ theory of denotation and connotation to explore how literal (denotative) and symbolic (connotative) meanings in the lyrics reflect deep psychological turmoil and existential anxiety. This research uses a qualitative descriptive method. The primary data consist of selected song lyrics by Gulch, and the theory of two orders of signification by Roland Barthes is used to decode the embedded meanings within the texts. This study also considers the emotional states and existential conflicts expressed through the lyrical characters. The findings reveal that Gulch’s song lyrics convey profound psychological conditions such as alienation, suicidal ideation, inner conflict, and loss of meaning. Through Barthes’ semiotic lens, these lyrics serve as metaphors for existential suffering and the modern individual’s struggle to find identity and purpose amidst chaos. The violent and surreal imagery, while intense, becomes a literary medium through which existential crises are expressed and interpreted.